2011
DOI: 10.1590/s1516-35982011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Association between the morphological and productive characteristics in the selection of elephant grass clones

Abstract: -The objectives in this work were to study the association between the morphological and productive characteristics in Pennisetum sp. clones, and to identify the morphological characteristics responsible for the productivity in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
0
21
0
2
Order By: Relevance
“…v.70, n.1, p.6-11, January/February 2013 Forages with greater potential for ensiling must have an adequate chemical composition for fermentation and increased productivity. Cunha et al (2011) also evaluated the dry matter yield of the same clones used in the current study and reported the following values: 6,258 kg ha -1 for Taiwan A-146 2.37, 4,952 kg ha -1 for Taiwan A-146 2.114, 5,756 kg ha -1 for Elephant B, 6,873 kg ha -1 for HV 241 and 4,465 kg ha -1 for Mott. Silva et al (2011a) evaluated five dwarf elephant grass clones.…”
Section: Resultsmentioning
confidence: 98%
“…v.70, n.1, p.6-11, January/February 2013 Forages with greater potential for ensiling must have an adequate chemical composition for fermentation and increased productivity. Cunha et al (2011) also evaluated the dry matter yield of the same clones used in the current study and reported the following values: 6,258 kg ha -1 for Taiwan A-146 2.37, 4,952 kg ha -1 for Taiwan A-146 2.114, 5,756 kg ha -1 for Elephant B, 6,873 kg ha -1 for HV 241 and 4,465 kg ha -1 for Mott. Silva et al (2011a) evaluated five dwarf elephant grass clones.…”
Section: Resultsmentioning
confidence: 98%
“…At planting, 110 kg P ha −1 and 100 kg K ha −1 were evenly distributed along the furrows. After fertilization, plots were subjected to five experimental cuts at 56 d of regrowth at 10 cm from the soil surface preceding the beginning of the experiment (Cunha et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Among the cultivars of elephantgrass generated in breeding programs, the dwarf types have morphological and yield differences (Cunha et al, 2011) compared with taller cultivars and have great potential for ruminant livestock production (Almeida et al, 2000b; Flores et al, 1993; Silva et al, 1994). Forage nutritive value coupled with the biomass yield makes elephantgrass an important alternative for livestock production systems, including small ruminants.…”
mentioning
confidence: 99%
“…The variable "number of tillers" gathered the largest number of families that met such condition, namely: Cameroon x Cuba-11; Cameroon x Guaçu/I.Z.2; Capim Cana D'África x Guaçu I.Z.2; CPAC x Cuba-115; Capim Cana D'África x Cuba-115; IAC-Campinas x IJ 7139; and IAC-Campinas x Guaçu/I.Z.2; when both assessment cuts were taken into consideration (Table 4). The number of tillers is relevant in studies that aim to increase the dry biomass production because there is a correlation between high genetic nature and dry matter production (Cunha et al, 2011). Only a single family, derived from the crossing between Cameroon x Guaçu/I.Z.2, showed plant height above the mean when both assessment cuts were taken into consideration.…”
Section: Resultsmentioning
confidence: 99%
“…According to Cunha et al (2011), such situation is favorable, because it is known that the elephant grass, like all forage plants, is subject to seasonality. Thus, it presents productivity variation in certain periods of the year.…”
Section: Resultsmentioning
confidence: 99%